Belajar dari Tradisi Para Sayid-Wali Songo di Nusantara: Learning from the Sayyids-Wali Songo’s Traditions in Nusantara - Ahmad Baso (Besari: Journal of Social and Cultural Studies, 2023)
Indonesian Islam has its own characteristics, being under the influence ofulama and kiai. The influence of these ulama on society has a big impact. Thespread of Islam in Indonesia in the 15th century was brought by Wali Songo.This research uses document research and direct reading methods fromprimary sources. In the spirit of preaching like this, the Wali Songo whospread Islam in this country are well aware that there is no use of spreadingIslam as a blessing if it turns out that the Indonesian people are experiencingdifficulties, are not harmonious, are destitute, are not living peacefully due tobeing at enmity with each other within the tribe. -ethnicity and race, so that itis not solid as a nation. In other words, Wali Songo's tolerance has its originsin the essence of the archipelago as Daru-s-Salam, especially in the substanceof the meaning of "anggelar adil palamarta" (realizing ultimate justice) toguarantee the implementation of the principles of a beneficial state. Islam Indonesia mempunya sifat tersendiri, berada di bawah pengaruh ulama dankiai. Pengaruh para Ulama ini pada masyarakat memiliki dampak yang besar.Penyebaran Islam di Indonesia pada abad 15 yang dibawa oleh Wali Songo. Dalampeneltian ini menggunakan penelitian dokumen dan metode membaca langsung darisumber primer. Dalam semangat dakwah seperti ini, para Wali Songo penyebarIslam di negeri ini sadar betul: bahwa tidak ada gunanya menyebarkan agama Islamsebagai rahmat kalau ternyata orang-orang Indonesia mengalami kesusahan, tidakrukun, melarat, tidak tenang hidup akibat bermusuhan satu-sama lain dalam sukusuku dan ras, hingga tidak solid sebagai sebuah bangsa. Dengan kata lain, toleransiWali Songo punya asal-usulnya dalam hakikat Nusantara sebagai Daru-s-Salam,khususnya pada substansi makna “anggelar adil palamarta” (mewujudkan keadilanyang utama) untuk menjamin pelaksanaan prinsip-prinsip bernegara yang maslahat.